Response of fusion plasma-facing materials to nanosecond pulses of extreme ultraviolet radiation. (31st August 2018) - Straus, Jaroslav; Kolacek, Karel; Schmidt, Jiri; Frolov, Oleksandr; Vilemova, Monika; Matejicek, Jiri; Jager, Ales; Juha, Libor; Toufarova, Martina; Choukourov, Andrey; Kasuya, Koichi
Abstract: The experimental study of damage to tungsten (W), molybdenum (Mo), and silicon carbide (SiC) surfaces induced by focused extreme ultraviolet laser radiation (λ 47 nm/ 1.5 ns/21–40 µJ) is presented. It was found that W and Mo behaved similarly: during the first shot, the damaged area is covered by melted and re-solidified material, in which circular holes appear – residua of just opened pores/bubbles, from which pressurized gas/vapors escaped. Next cracks and ruptures appear and the W has a tendency to delaminate its surface layer. Contrary, single-crystalline SiC has negligible porosity and sublimates; therefore, no escape of "pressurized" gas and no accompanying effects take place. Moreover, SiC at sublimating temperature decomposes to elements; therefore, the smooth crater morphology can be related to local laser energy density above ablation threshold. When more shots are accumulated, in all three investigated materials, the crater depth increases non-linearly with number of these shots. The surface morphology was investigated by an atomic force microscope, the surface structure was imaged by a scanning electron microscope (SEM), and the structure below the surface was visualized by SEM directed into a trench that is milled by focused ion beam. Additionally, structural changes in SiC were revealed by Raman spectroscopy.